Effect of Triacylglycerol Compositions and Physical Properties on the Granular Crystal Formation of Fat Blends. (30th October 2018) - Shimomura, Yuichi; Tsuchiya, Miki; Ueno, Satoru; Shiota, Makoto
Abstract: The effect of triacylglycerol (TAG) compositions and physical properties related to solid fat content (SFC) on the behavior of granular crystal formation was investigated. Four fat blends involving different 1, 3‐dipalmitoyl‐2‐oleoyl‐ sn ‐glycerol (POP) and 1‐palmitoyl‐2, 3‐dioleoyl‐ sn ‐glycerol (POO) compositions or SFC were prepared, and crystallization was investigated using polarizing microscopy, X‐ray diffraction, SFC, whereas hardness was determined using a texture analyzer. Samples containing a higher saturated fatty‐acid content from palm and higher SFC showed higher β‐type crystals in the initial period, yielding a number of small‐sized crystals, with no growth occurring afterward. Growth of the granular crystals as a function of time was observed in the samples, transforming from the β'‐ to β‐type polymorph gradually. Large granular crystals at the initial stage were observed in the sample with a higher POO content and lowest SFC. These results suggested that POO promotes the rate of the crystals' polymorphic transformation, resulting in the growth of granular crystals. In contrast, excess high‐melting‐point TAG content, such as tripalmitin and POP, retarded granular crystal growth regardless of the increased β' to β transition rate. We concluded that the behavior of the growth of granular crystals is influenced by the combined effect of TAG composition and SFC.